Interpreting visitor experiences with digital cultural heritage exhibitions in Yimeng China through thematic analysis - Li, Yue; Li, Tiantian; Bai, Yue; Ismail, Nor Atiah; Chen, Jinjin; Wei, Taoyu; Salarzadeh Jenatabadi, Hashem (Nature Research, 2025)
Yimeng cultural heritage landscapes are a crucible of regional identity, historical memory, and dynamic nodes in the context of heritage, tourism, and digital innovation. In the context of sustainable cultural tourism in the digital age, in general, this paper aims to explore the operation mechanism of visitor experience and meaning making of digital exhibitions in the cultural heritage landscape of Yimeng. Building on the Knowledge, Attitude, and Perception (KAP) framework, this work investigates how digital components—such as virtual reconstruction, multimedia storytelling, and interactive exhibits— influence the cognitive understanding (knowledge), evaluative responses (attitudes), and lived experiences (perceptions) of cultural stories by tourists. A qualitative method was employed, and 22 semi-structured interviews were conducted with visitors at the major display sites in Yimeng. Thematic analysis, conducted with the support of the MAXQDA software, generated five primary themes: Authenticity, Preservation, and Cultural Integrity, Emotional Resonance and Psychological Impact, Cultural Recognition and Valuation Enhancement, Community and Environmental Sustainability, and Future Directions and Enhancements. The themes present the everyday encounters and interpretive narratives that tourists create within these digital interactions, and in doing so, suggest how these technologies can facilitate cultural meaning-making, participatory learning, and emotional attachment to heritage. The findings are practically valuable for heritage practitioners, digital content developers, and policymakers who aim to develop inclusive and engaging digital heritage environments for cultural sustainability and meaningful visitor connection, as well as improved KAP outcomes.